A Review on Common Factors Affecting a Semen Quality of Male - Dubey, Chetan Kumar; Sharma, Archana; Khinchi, M. P. (Asian Journal of Pharmaceutical Research and Development, 2017)
Reproductive disorder and infertility is emerging globally as serious medical and social problem. It is not just the women that need to be in good shape, men also need to be healthy and fertile to have the optimum chance of having an offspring. It is estimated that one of five couples are affected by some degree of infertility. Males are exposed to various factors which may decrease their reproductive capabilities. Hormonal imbalances, illness, reproductive anatomical abnormalities, sexual dysfunction and psychological problems can temporarily or permanently affect male reproductive system leading to infertility. Male reproductive toxins can be encountered in many ways- industrially, environmentally, biochemically, hormonally, genetically, therapeutically, self-administered and life style. The objective of the present review is to summarize results to date of studies examining the adverse effects of various factors on human sperm parameters, morphology of reproductive organs, DNA damage and chromosomal aberrations related to male reproductive system.